Perceptions of Stalking: Examining Perceivers’ Country of Origin, Perpetrator-Target Prior Relationship, and the Mediating Effect of Victim Responsibility - Chung, Kai Li (Journal of interpersonal violence, 2022)
Research in stalking perceptions has shown certain relational biases, in which people tend to view ex-partner stalkers to be less dangerous than stranger or acquaintance stalkers. These findings are in direct contrast to those of real-life cases whereby ex-partner stalkers pose a greater threat. In addition, although stalking is recognized as a global social problem, most studies have been based on samples drawn from Western, educated, industrialized, rich, and democratic countries. The current study examined whether the prior relationship between the stalking perpetrator and target influences people?s perceptions of stalking and whether cross-national differences exist between participants based in Malaysia (where there is currently no law that criminalizes stalking) and England (where stalking has been outlawed since 1997). In a 3 ? 2 between-subjects design, 294 Malaysian participants and 170 English participants were presented with a vignette describing a stalking scenario in which the perpetrator was depicted as a stranger, acquaintance, or ex-partner. Participants judged the extent to which the perpetrator?s behavior constitutes stalking; necessitates police intervention; would cause the victim alarm or personal distress; would cause the victim to fear the use of violence; and can be attributed to encouragement on the part of the victim. Results showed that typical relational biases existed in both samples, but Malaysian participants were less likely than their English counterparts to label any harassing scenario as serious. Perceptions of victim responsibility were found to mediate the effect of prior relationship and nationality on participants? perceptions. The findings point to the urgency of better cross-cultural understanding of harassment behavior as well as legislations against stalking.